The effects of prefrontal vs. parietal cortex transcranial direct current stimulation on craving, inhibition, and measures of self-esteem - Ljubisavljevic, Milos; Basha, Jonida; Ismail, Fatima Y. (Frontiers in Neuroscience, 2022)
We examined the effects of transcranial direct current stimulation (tDCS), dorsolateral prefrontal cortex (DLPFC), and inferior parietal lobule (IPL) on craving state and trait, inhibition and subjective psychological aspects like body image and self-esteem state and trait. tDCS was administered at 1.5 mA for five days, 20 min each day (two rounds of 10 min divided by a 10 min mindfulness task break) to DLPFC, IPL, or as SHAM stimulation. To decompose immediate and cumulative effects, we measured inhibition through the Go/no-go task along with craving, self-esteem and body appreciation through a battery of questionnaires on days 1 and 5. We found that false alarm errors decreased in the DLPFC group, increased in IPL, and remained the same in the SHAM group. There was trending reduction in craving trait in all groups, while momentary craving was decreasing in DLPFC and increasing in IPL, not reaching significe. Self-esteem state and body perception was also improved in IPL according to time and baseline. Instead, there was a significant improvement in self-esteem trait over time in DLPFC and IPL, possibly due to the mindfulness exercise. These preliminary results indicate that tDCS modulates inhibition in fronto-parietal areas with opposite effects, enhancing it in DLPFC and impairing it in IPL. Moreover, craving is moderately linked to inhibition or self-esteem and body appreciation which seem to be not affected by neuromodulation but may rely on broader regions as more complex constructs. Finally, fractionated protocol can be effectively used to influence inhibition with milder effects on the other constructs.